Ex Ante Costs of Violating Absolute Priority in Bankruptcy - Bebchuk, Lucian Arye (Journal of Finance, 2002)
ABSTRACT A basic question for the design of bankruptcy law concerns whether value should be divided in accordance with absolute priority. Research done in the past decade has suggested that deviations from absolute priority have beneficial ex ante effects. In contrast, this paper shows that ex post deviations from absolute priority also have negative effects on ex ante decisions taken by shareholders. Such deviations aggravate the moral hazard problem with respect to project choice‐increasing the equityholders incentive to favor risky projects‐as well as with respect to borrowing and dividend decisions.